An Analysis of Values in Social Life in Snowpiercer Movie - Putri, Chinta Ade; Damayanti, Indah; Hardiah, Mei (Journal of English Education and Teaching, 2024)
This research aimed to find out how the lower class and the upper class are represented in the Snowpiercer movie as well as to find out how the Snowpierce movie portrays values in social life in. Library research (documentation) and descriptive qualitative method were used to conduct the research. The data findings were found by using script and dialogues from the movie and were also identified by using values in social life according to Nurgyantoro (1995:331). The results showed that: 1) there were 2 scenes from the movie that showed how the lower class and the upper class were represented, the 2 scenes described the lower class and the upper class as a shoe and a hat. A shoe was to described the lower class and a hat was to described the upper class. 2) there were 8 scenes from the movie that portrayed Justice values in social life which all 8 scenes showed that Justice values in social life was being ignored. 3) there was 1 scene from the movie that portrayed Frienship values in social life which occured among the people of the lower class. 4) the Harmony values in social life between the lower class and the upper class could not be portrayed in the movie.